Pyrogallol-Phloroglucinol-6, 6-Bieckol Restored Primary Cilia Length, Which Was Decreased by High-Fat Diet in Visceral Adipose Tissue, and Decreased Adipogenesis - Seyeon Oh; Myeongjoo Son; Ji Tae Jang; Chul Hyun Park; Kuk Hui Son; Kyunghee Byun (International Journal of Endocrinology)
Length of primary cilia, which involves cell cycle reentry and disassembly of cilia, promotes cell mitosis. It is known that the cilia length in adipose tissue of the high-fat diet (HFD) animals was shortened and accompanied by increased adipogenesis. Male C57BL/6N mice were randomly divided into groups. The mice group was given the normal fat diet (NFD/saline), HFD mice group for 4 weeks, and then HFD was also treated for the next 4 weeks with saline (HFD/saline), Ecklonia cava extract (HFD/ECE), or pyrogallol-phloroglucinol-6, 6-bieckol, a segment of ECE (HFD/PPB). We evaluated the effect of ECE and PPB on modulating cilia length of visceral adipose tissue and decreasing adipogenesis by decreasing cell cycle reentry using an HFD-fed mouse model. ECE and PPB decreased physiological changes, which increased by HFD, but ECE and PPB decreased the upregulation of the IL-6/STAT3/AURKA signaling pathway, which is involved in cilia disassembly. In addition, ECE or PPB elongated the cilia and decreased cyclin A2 and Cdk2 expression, which promote cell cycle reentry, and decreased the adipogenesis genes. PPB and ECE restored cilia length and decreased adipogenesis through modulating the IL-6/STAT3/AURKA pathway and decreasing cell cycle reentry in the visceral adipose tissue of HFD/saline mice group.